2016
DOI: 10.1007/s00482-016-0130-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiologische Mechanismen bei der Pathophysiologie chronischer viszeraler Schmerzen

Abstract: Although visceral pain is of high clinical relevance, it remains poorly understood especially when compared to somatic pain. Nevertheless, interdisciplinary research approaches bridging psychophysiology and neurogastroenterology have contributed to a more refined knowledge about the complex peripheral and central mechanisms of the bidirectional brain-gut axis in recent years. This review summarizes current knowledge regarding psychobiological mechanisms in the pathophysiology of chronic visceral pain in functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In many patients, pathophysiological characteristics such as altered GI motility and visceral hypersensitivity, but also altered central pain processing have been reported . These findings can potentially be explained by an altered function of the nervous system, such as a dysfunctional afferent signaling, dysfunctional central pain processing or increased responsiveness to environmental factors such as stress . Due to these observations, the brain‐gut axis, ie, the bidirectional brain‐gut communication network, has become focus of recent research and is a promising candidate in the quest to improve the understanding of IBS pathophysiology …”
Section: Introductionmentioning
confidence: 99%
“…In many patients, pathophysiological characteristics such as altered GI motility and visceral hypersensitivity, but also altered central pain processing have been reported . These findings can potentially be explained by an altered function of the nervous system, such as a dysfunctional afferent signaling, dysfunctional central pain processing or increased responsiveness to environmental factors such as stress . Due to these observations, the brain‐gut axis, ie, the bidirectional brain‐gut communication network, has become focus of recent research and is a promising candidate in the quest to improve the understanding of IBS pathophysiology …”
Section: Introductionmentioning
confidence: 99%
“…Visceral hypersensitivity is a hallmark of irritable bowel syndrome and other gastrointestinal disorders that cause pain. The mechanism of visceral hypersensitivity and pain is still poorly understood due to the diverse nature of visceral hypersensitivity compounded by multiple factors such as sexual dimorphism, psychological and physical stresses, genetic and epigenetic traits, and the nature of predisposed disease ( Chen et al, 2015 ; Elsenbruch and Enck, 2016 ). We recently demonstrated that early life stresses, for example, neonatal colorectal distension (CRD), maternal separation, could induce visceral hypersensitivity in rats ( Wang et al, 2016 ; Zhang et al, 2016a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal mucosal immune system is composed of intestinal epithelial cells, intestinal interepithelial lymphocytes, lymphocytes of the lamina propria, intestinal submucosal-collecting lymph nodes, and various monocytes, which directly participate in intestinal immune regulation. Some studies have confirmed the presence of abnormal mucosal immunity in patients with IBS (Aerssens et al, 2008 ), and stress factors are thought to be strongly associated with the development of IBS (Elsenbruch and Enck, 2016 ). Stress regulates the intestinal immune system by triggering the brain–gut axis to produce neurotransmitters and hormones.…”
Section: Abnormal Immune Systemmentioning
confidence: 96%